PROGRAM LIFE SKILL BIDANG MULTIMEDIA BAGI ANAK DIDIK PERMASYARAKATAN LEMBAGA PEMBINAAN KHUSUS ANAK (LPKA) PALEMBANG SEBAGAI BEKAL PENGEMBANGAN POTENSI SUMBER DAYA MANUSIA - Wahyu Kurnia Sandi; Renata Jorgy Pratama; Mutiara Ramadhona; Ahmad Asyaari; Deevy Marentika Dinsi Ulan Dari; Mustika Mustika (LPPM IKIP Jember, 2018)
LPKA class 1 Palembang Prison students who are still in education continue to continue their education, and are given skills training such as; karate, scout, hair clipping skills, automotive training, basic computer training, furniture crafts and gardening skills. Coaching is done is good enough but still not in accordance with the current digital era. In the digital age children (adolescents) are accustomed to using cameras and computers, this ultimately gives the impact of advanced business or business opportunities in the field of multimedia. Photography and video editing is a science that goes into multimedia clusters. To produce valuable photographic products required special skills such as how to operate and take pictures using professional digital camera and handycam, and the process of editing using a computer. To acquire such skills, training in photography is required. The use of adobe photoshop application and adobe premiere can be learned by anyone including correctional students. The results of this activity are prison students can use cameras and produce photos and videos, prison students can edit photos with photoshop and edit video with premiere, prison students have the will to entrepreneurship in the multimedia field after the detention period. Although the implementation still has an inhibiting factor but the implementation activities performed 100% well.